Oxytocin Protects PC12 Cells Against β-Amyloid-Induced Cell Injury - Mohammed Mufadhe Alanazi; Awatif B. Albaker; Lamia A. Alzaagi; Jawza F. Alsabhan; Fawaz Alasmari; Mohammed M. Almutairi; Metab S. Alharbi; Abdullah F. Alasmari; Faleh Alqahtani; Sary Alsanea (Pharmaceuticals)
Background/Objectives: Neurodegenerative diseases, particularly Alzheimer’s disease (AD), are characterized by progressive cognitive decline and non-cognitive symptoms that significantly affect health and quality of life. Beta-amyloid (Aβ) protein accumulation is a key factor in AD pathology, leading to neuronal damage. Oxytocin (OXT), a neuropeptide with neuroprotective potential, has garnered interest owing to its ability to mitigate neurotoxicity. We hypothesized that oxytocin could protect PC12 cells from Aβ-induced cytotoxicity through antioxidant effects and modulation of apoptotic pathways (i.e., mitochondrial and MAPK pathways). In this study, we aim to assess oxytocin’s protective effects on cell viability, oxidative stress, mitochondrial function, and apoptotic signaling. Methods: PC12 cells were treated with Aβ25–35 and pre-treated with varying oxytocin concentrations to assess cell viability, reactive oxygen species (ROS) generation, and mitochondrial membrane potential. Western blotting was performed to analyze the effects on mitochondrial apoptosis and MAPK pathways. Results: Oxytocin treatment significantly improved cell viability in a dose-dependent manner and reduced Aβ-induced oxidative stress and mitochondrial dysfunction. Oxytocin-treated groups exhibited decreased ROS levels, increased mitochondrial membrane potential, and modulation of apoptosis-related proteins. Oxytocin upregulated phosphorylated ERK1/2 and Bcl-2 while downregulating BAX and caspase-3, reducing the BAX/Bcl-2 ratio. Conclusions: Oxytocin effectively protects PC12 cells from Aβ-induced neurotoxicity, highlighting its potential as a therapeutic agent for AD. Further research is needed to clarify oxytocin’s mechanisms and clinical implications in AD treatment.